شیکاری دیارترین جۆرەکانی تۆن لەڕۆمانی: )گرەوی بەختی هەاڵڵە(ی عەتای نەهاییدا - کاکی, پ.د. حەمەنوری عومەر; ابراهیم, کامیل قانع (Sulaimani Journal for Humanities, 2023)
Tone has its own role and significance in literature because the writer, through tone and its various types, can convey their general and specific intentions, and certain messages behind their text to the reader. From this perspective, tone in literature can affect, excite, and move the reader since tone as a channel and literary technique, and linguistic device plays a vital role in expressing the writer’s mood through his work. Hence, studying tone as an artistic device is crucial. Though, it should be noted that each writer uses tone differently. Regarding his outlook and information about tone as a technique, each author benefits from it according to the content of his work. Tone in literature, as a new technique and art has linguistic dimensions. So, this subtle and effective technique can be shown in writing through language.